THE RELATIONSHIP OF MALOCCLUSIONS WITH THE ERUPTION TIME OF PERMANENT TEETH IN CHILDREN LIVING IN DIFFERENT CLIMATIC AND GEOGRAPHICAL CONDITIONS - Smaglyuk, L.V.; Chukhray, N.L..; Bezvushko, E.V.; Miskiv, A.L.; Shpotyuk, O.O. (World of Medicine and Biology, 2020)
The article highlights the prevalence and structure of malocclusion and terms of eruption of the permanent teeth in children living in different climatic and geographical conditions. It has been established that the prevalence of malocclusion and terms of eruption of the permanent teeth in children depends on the geographical and environmental living conditions. It is proved that there is a strong correlation between malocclusions and the number of erupted teeth.